Heuristic approach to allocation of trucks in a transportation system - Takeno, Takeo; Matsui, Kenichiro; Yamazaki, Genji; Ishikawa, Toshihiro (Computers & Industrial Engineering, 1994)
This paper considers the problem of how luggages should be assign to each truck for the transportation system consists of a depot, a fixed area and two types of luggages, called schedule problem. The main purpose of this paper is to propose a procedure for the problem subject to keep the balance of work loads among truck drivers. The procedure is based on 3 (heuristic) rules for replacing the addresses of each luggage with the ‘ conventional address,’ converting size of each luggage into ‘ weight’ and introducing a measure to keep the balance of work loads. The procedure consists of three stages according to ‘ priority’ of the types of luggages. A case study is presented that demonstrate the practical usefulness of the procedure.